Anterior abdominal wall metastasis following curative resection and chemoradiation of rectal cancer masquerading as a desmoid tumour: A clinical conundrum. Issue 1 (February 2022) - Raveendranadh, Ajay; Goutham, Meera; Gowda, Chiranth; Hegde, Kshama; Monappa, Vidya; Rodrigues, Gabriel
الملخص: يحدث الورم الرباطي لجدار البطن الأمامي (الغمد المستقيم) بشكل شائع عند النساء بعد جراحة البطن. من النادر حدوث نقيلة من سرطان القولون والمستقيم إلى جدار البطن الأمامي وينتج عنه معضلة علاج معقدة. نقدم امرأة تبلغ من العمر ٥٧ عاما كانت قد خضعت لعملية استئصال أمامية منخفضة بالمنظار وإجراء علاج إشعاعي كيميائي مساعد في عام ٢٠١٣. وبعد سبع سنوات، ظهرت عليها كتلة في جدار البطن الأمامي بدون أعراض. سريريا، بدا أن الورم هو ورم رباطي. وتم إجراء استئصال موضعي واسع للورم وأظهر التشريح المرضي النهائي وجود نقيلة ورمية (سرطانة غدية). مع العلاج الكيميائي المساعد، أصبح المريض الآن خاليا من الورم وفي صحة جيدة. يجب أن يؤخذ في الاعتبار احتمال حدوث نقيلة ورمية لدى جميع المرضى، حتى عند من خضع لاستئصال علاجي مع استخدام العلاج الإشعاعي الكيميائي المساعد لسرطان القولون والمستقيم. Abstract: Desmoid tumour of the anterior abdominal wall (rectus sheath) commonly occurs in women post abdominal surgery. Metastasis from colorectal cancer to the anterior abdominal wall, on the other hand, is rare and produces a complex management dilemma. This Case study presents a 57-year-old woman who received a curative laparoscopic low anterior resection and adjuvant chemoradiation in 2013. Seven years later, she presented with an asymptomatic anterior abdominal wall lump. Clinically, the lump appeared to be a desmoid tumour. A wide local excision of the lump was carried out and the final histopathology showed a metastatic lesion (adenocarcinoma). With adjuvant chemotherapy, the patient is now disease-free and doing well. A possibility of distant metastasis must be kept in mind for all patients, even when they have undergone curative resection with adjuvant chemoradiation for colorectal cancer.